Statistics (IntechOpen, 2023)
Since data grows faster than ever, the role of statistics becomes more and more crucial nowadays, and there is no doubt that statistics will be even more critical in the future. The application of statistics is extensive, and in our daily lives there is almost no human activity where the use of statistics is not needed. In this limited volume, we try to cover as many as different and multidisciplinary fields in statistics as possible and aim to present recent developments and applications of statistical analysis. Therefore, this book is organized into three sections: "The Role of Statistics on Quantification," "Applications of Statistics on Economics and Development," and "Applications of Statistics on Various Topics."